The effects of fresh leaf-to-water ratio and heating time on the antifungal and antioxidant activities of betel leaf (Piper betle L.) extract - Sartini Sartini; Nurdiah Khaerawati; Rezky Amalia Kamril; Novi Febriani (Pharmaciana, 2020)
More than half of the Indonesian people use herbal medicines to maintain their health, including ones that are served immediately after preparation or also known as jamu gendong. This plant-based medicine is prepared traditionally by boiling using different ratios of leaves to water and heating time. The study was designed to determine the heating time and the fresh leaf-to-water ratio that exhibited the highest antioxidant and antifungal activities against Candida albicans. Fresh betel leaves were extracted by boiling and infusion methods, with the ratio of 1:5 and 1:10 and the heating time of 5 and 10 minutes for boiling and 15 minutes for infusion. The excess water in the resulting extract was removed using a freeze dryer, then the total phenolic content was determined by Folin-Ciocalteu spectrophotometry. Meanwhile, the antioxidant and antifungal activities were tested by the DPPH method and microdilution, respectively. The results showed that betel leaf extract with the highest yield and polyphenol content was obtained by infusion with the sample-to-water ratio of 1:10, and this was positively correlated with antioxidant activity against DPPH (IC50= 17.4 ppm) and antifungal effect against Candida albicans (MIC= 0.5%).Â